Hybrid surgery recanalization for high-level chronic internal carotid artery occlusion - Cai, Yuankun; Zhang, Tingbao; Wang, Lesheng; Li, Xiang; Wei, Wei; Feng, Yu; Li, Guo; Ma, Yihui; Chen, Xinjun; Zhao, Wenyuan; Chen, Jincao (Frontiers in Neurology, 2023)
Objective: Although endovascular recanalization is considered a more effective treatment for chronic internal carotid artery occlusion (CICAO), the success rate of C and D type CICAO remains inadequate. We present hybrid surgery (carotid endarterectomy combined with carotid stenting) for C and D type CICAO, and explore the influential factors and effects of hybrid surgery recanalization. Methods: We retrospectively analyzed the clinical, imaging and follow-up data of 22 patients with C and D type CICAO treated by hybrid surgery at the Zhongnan Hospital of Wuhan University from December 2016 to December 2020. We also summarize the technical points related to hybrid surgery recanalization. Results: 22 patients with C and D type symptomatic CICAO underwent hybrid surgery recanalization. There were no postoperative deaths in all patients after hybrid surgery recanalization. Nineteen patients were successfully recanalization with a success rate of 86.4% and three cases with a failure rate of 13.6%. Patients were divided into the success and the failure groups. Significantly different radiographic classification of lesions was observed between the success group and the failure group (P = 0.019). The rates of CICAO with reverse ophthalmic artery blood flow in ICA preoperatively were 94.7% in the success group and 33.3% in the failure group, respectively (P = 0.038). Three cases of hybrid surgery recanalization failure were transferred for EC-IC bypass and had good neurological recovery. Postoperative average KPS scores of the 19 patients were improved compared to the preoperative ones (P < 0.001). Conclusion: Hybrid surgery for C and D type CICAO is safety and effective with a high recanalization rate. The recanalization rate is related to whether the occluded segment surpasses the ophthalmic artery.